THE INFLUENCE OF EXPORT IMPORT SERVICE QUALITY AND SERVICE FACILITIES ON EMPLOYEE PERFORMANCE - Haeruddin Haeruddin (Universitas Islam Lamongan, 2024)
The aim of this research is to determine and analyze partially and simultaneously the influence of quality of export and import services and service facilities on employee performance at the Madya Customs and Excise Service and Supervision Office, Type B Makassar. The total population at the Makassar Customs and Excise Supervision and Services Office, Type B, Madya Customs, is 127 employees and the sample uses the Slovin formula method with the total sample obtained being 96 people. The research method uses a quantitative descriptive approach and hypothesis testing uses the multiple linear regression method. The research results showed that: (1) The quality of export and import services has a positive and significant effect on employee performance at the Customs and Excise Supervision and Service Office, Madya Customs B Makassar (2) Service facilities have a positive and significant effect on employee performance at the Supervision and Service Office. Customs and Excise Intermediate Type Customs B Makassar, (3) Quality of Export and Import Services and Service Facilities Simultaneously has a positive and significant effect on Employee Performance at the Customs and Excise Supervision and Service Office Type Intermediate Customs B Makassar.